Hankel determinant for the class of K(α, β) - Maslina Darus,; Imran Faisal, (Penerbit Universiti Kebangsaan Malaysia, 2010)
Let f(z)=z+∑anzn be an analytic function in the open unit disc. A sharp upper bound is obtained for the functional |a2a4-a23| for the class k(α,β) of normalised close-to-convex functions defined in the open unit disc